Biostratigraphic significance of the calcareous nannofossil genus Reticulofenestra in the Upper Pliocene of the North Atlantic - Koji Kameo; Toshiaki Takayama (PANGAEA, 1999)
We demonstrate size fluctuations of the calcareous nannofossil genus Reticulofenestra in Upper Pliocene sediments from the North Atlantic Ocean and clarify a characteristic evolutionary trend of this genus. Four bioevents, which are based on abrupt decreases in maximum size and on changes of morphologic features of Reticulofenestra specimens, are detected in the sediments. They are the disappearance of R. minutula var. A, the termination of Acme Zone II of R. minutula var. C, the disappearance of R. minutula var. B, and the termination of Acme Zone I of R. minutula var. C, in ascending order. These are nearly synchronous and traceable events.
Supplement to: Kameo, K; Takayama, T (1999): Biostratigraphic significance of sequential size variations of the calcareous nannofossil genus Reticulofenestra in the Upper Pliocene of the North Atlantic. Marine Micropaleontology, 37(1), 41-52, https://doi.org/10.1016/S0377-8398(99)00009-2